2000
DOI: 10.1038/sj.bjp.0703630
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐2 adrenoceptors are present in rat aorta smooth muscle cells, and their action is mediated by ATP‐sensitive K+ channels

Abstract: 1 The role of a 2 -adrenoceptors in the response of aorta smooth muscle rings to the a 2 -adrenoceptors agonists UK 14,304 and clonidine was studied. 2 Stimulation by 1 ± 10 nM UK 14,304 caused dose-dependent relaxant responses in BaCl 2 -contracted endothelium-denuded aorta rings, and hyperpolarization in rings with or without endothelium, which were inhibited by yohimbine and glibenclamide, but not aected by prazosin, propranolol, apamin or iberiotoxin. At higher concentrations (10 nM ± 10 mM) UK 14,304 also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…The lack of an effect of TTX on the aortic resting tension, together with the fact that membrane depolarization induced by the addition of low concentrations of KCl (2–15 mmol/L) is required to unmask this component of contraction, reveals that Na v channels are closed at physiological RMPs. Our measurement of the RMP (−56 mV) is consistent with other reports [33], [34] and with the estimated activation threshold of the Na v 1.2 isoform; that is between −60 mV and −50 mV [35], [36]. Interestingly, the window current determined by the overlap of the steady-state activation and inactivation curves of the Na v 1.2 isoform is expected to generate a persistent influx of Na + between the activation threshold (between −60 mV and −50 mV) and −40 mV [35], [36].…”
Section: Discussionsupporting
confidence: 93%
“…The lack of an effect of TTX on the aortic resting tension, together with the fact that membrane depolarization induced by the addition of low concentrations of KCl (2–15 mmol/L) is required to unmask this component of contraction, reveals that Na v channels are closed at physiological RMPs. Our measurement of the RMP (−56 mV) is consistent with other reports [33], [34] and with the estimated activation threshold of the Na v 1.2 isoform; that is between −60 mV and −50 mV [35], [36]. Interestingly, the window current determined by the overlap of the steady-state activation and inactivation curves of the Na v 1.2 isoform is expected to generate a persistent influx of Na + between the activation threshold (between −60 mV and −50 mV) and −40 mV [35], [36].…”
Section: Discussionsupporting
confidence: 93%
“…In rat aorta smooth muscle, it has been recently reported that UK 14304 (1–30 n m ) and clonidine (0.1–3 n m ) produced relaxation in endothelium‐denuded aortic rings contracted with BaCl 2 , which was inhibited by yohimbine; whereas UK 14304 provoked contraction with higher concentrations (≥100 n m ), which was inhibited by prazosine [19]. The authors [19] concluded that low concentrations of α 2 ‐AR agonists (clonidine and UK 14304) induced relaxation activating smooth muscle α 2 ‐AR, whereas high concentrations may also activate α 1 ‐AR. On the contrary, our results obtained with serotonin‐ and PGF 2 α ‐contracted aortic tissues, clearly showed that low concentrations of clonidine and UK 14304 (≤100 n m ) did not produce relaxant responses, neither in the presence nor in the absence of endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…As augmentation of the twitch contractions induced by clonidine was inhibited by yohimbine, the augmenting action of clonidine involves α2 receptor stimulation of vascular smooth muscle cells. The presence of α2 receptors on smooth muscle cells of vascular muscle has been reported (Fauaz et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine is known to dilate various arteries and veins via both endothelium-dependent and -independent pathways (Angus et al, 1986;Thorin et al, 1998;Nishina et al, 1999;Lui et al, 2000;Fauaz et al, 2000). Figueroa et al (2001) reported that endothelial α2D subtype receptors were coupled to the NO synthetic pathway in the mesenteric artery of the rat.…”
Section: Introductionmentioning
confidence: 99%